2013
DOI: 10.1039/c3cc39019e
|View full text |Cite
|
Sign up to set email alerts
|

Aryl iodides as strong inhibitors in gold and gold-based bimetallic quasi-homogeneous catalysis

Abstract: The strong inhibitor effect of aryl iodides on the quasi-homogenous gold-catalyzed oxidation reaction was described. Aryl iodides were adsorbed on the exposed surface of Au clusters, which affected the accessibility of the nanoclusters to the reacting species and acted as strong inhibitors in catalysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 22 publications
2
18
1
Order By: Relevance
“…Moreover, the bimetallic NC had a higher catalytic activity towards chloroarenes than the bromo equivalents (Scheme c). For example, a comparison of the observed reaction rates for the decay of chlorotoluene ( k C−Cl ) and bromotoluene ( k C−Brl ) showed that the value of k C−Cl (5.6×10 −2 h −1 ) was nearly three times that of k C−Brl (2.0×10 −2 h −1 ) . The significant differences in the rates of activation of C−Cl and C−Br showed an unprecedented halide dependence on the catalytic activity of bimetallic gold/palladium catalyst, otherwise the order of reactivity should be ArBr>ArCl.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the bimetallic NC had a higher catalytic activity towards chloroarenes than the bromo equivalents (Scheme c). For example, a comparison of the observed reaction rates for the decay of chlorotoluene ( k C−Cl ) and bromotoluene ( k C−Brl ) showed that the value of k C−Cl (5.6×10 −2 h −1 ) was nearly three times that of k C−Brl (2.0×10 −2 h −1 ) . The significant differences in the rates of activation of C−Cl and C−Br showed an unprecedented halide dependence on the catalytic activity of bimetallic gold/palladium catalyst, otherwise the order of reactivity should be ArBr>ArCl.…”
Section: Resultsmentioning
confidence: 99%
“…The second active site is the surface of Pd nanoparticles acting as a coupling site. It is well‐known that Pd nanoparticles were inactive for the Ullmann‐coupling of chloroarenes . However, Pd nanoparticles could be active for the Ullmann coupling when Pd nanoparticles were made smaller and impregnated on active supports such as La 2 O 3 .…”
Section: Resultsmentioning
confidence: 99%
“…The activation of carbon‐chlorine bond in the oxidative addition on Pd is generally difficult, compared to that of carbon‐bromine or carbon‐iodine due to the high dissociative energy of carbon‐chlorine bond. A success story of the activation of carbon‐chlorine in the Ullmann coupling of chloroarenes was reported by Sakurai and co‐workers by running the experiments in the presence of bimetallic AuPd alloy nanoclusters supported by poly( n ‐vinylpyrrolidone) (PVP) as a catalyst under ambient temperature . The unusual character of the bimetallic AuPd alloy nanoclusters, which exhibit a higher catalytic activity towards chloroarenes than bromoarenes and iodobenzene, is much more interesting.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, 4-NO 2 iodobenzene can give the corresponding symmetrical products with a yield of 88.6% in 2 h (entry 11). However, Dhital et al 24,61 reported that Au-Pd alloy nanoclusters stabilized by PVP could efficiently catalyze the Ullmann coupling of chloroarenes but not for bromoarenes and iodide arenes, and aryl iodide was a stronger inhibitor by forming a stable complex with a gold component. Obviously, the asprepared PdAu/NCB catalysts are more stable and adaptable to different substrates.…”
Section: Ullmann Coupling Reactionmentioning
confidence: 99%